ANTECEDENTS OF EMPLOYEE’S AFFECTIVE COMMITMENT THE DIRECT EFFECT OF WORK STRESS AND THE MEDIATION OF JOB SATISFACTION - Luturlean, Bachruddin Saleh; Prasetio, Arif Partono (Universitas Brawijaya, Indonesia, 2019)
This study aimed to investigate the effect of work stress on affective commitment directly and indirectly through the mediation of job satisfaction. Organizations need to develop employee's affective commitment. This emotional attachment believed to have positive impact on organizational performance. The current study examined 428 participants from various industries in Indonesia. Using path analysis the study revealed that work stress had very small negative effect on job satisfaction. Job satisfaction had significant positive effect on affective commitment, but work stress did not have significant effect on affective commitment. Thus job satisfaction did not mediate the effect of work stress on affective commitment. Findings suggest that organization still need to find other factors which have impact on employee's affective commitment, while they can still achieve affective commitment by providing a program that enhances job satisfaction. The contribution of this paper is to provide wider analysis regarding stress and job attitude to improve organizational policies in managing human resources.